Observations on the embryonic development of the mud crab, Scylla paramamosain - Xu, Li-Kun; Ma, Ke-Yi; Zhang, Feng-Ying; Wang, Wei; Ma, Ling-Bo; Jin, Zhong-Wen; Zhao, Ming; Chen, Wei; Fu, Yin; Ma, Chun-Yan; Liu, Zhi-Qiang (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain, we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo’s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.